Serum Selenium Concentration in Cervical Cancer Patients: Preliminary Study and Literature Review - Leri Septiani; Yudi Mulyana Hidayat; Mutakin Mutakin; Rizky Abdulah; Ahmad Faried; Hiroshi Koyama (Faculty of Medicine Universitas Padjadjaran, 2016)
Objective: To analyze the role of selenium and glutathione peroxidase (GPx) in cervical cancer.Methods: Serum selenium concentrations and GPx activities of 19 women with cervical cancer along with their healthy counterparts (control group) were obtained. Selenium concentration were measured fluorometrically and GPx activities were measured spectrophotometrically based on the quantity of NADPH used in the reduction of glutathione. Results: The mean of serum selenium concentrations in cervical cancer group was significantly lower than that in the control group, 67.24±15 ng/mL and 77.05±12 ng/mL (p=0.03), respectively. The mean GPx activity in the cervical cancer group was also significantly lower than that in the control group, 128.18±38 ∆mmol NADPH/min/L and 148.9±23 ∆mmol NADPH/min/L (p=0.04), respectively. Multivariate analysis in the cervical cancer patients showed that the Fédération Internationale de Gynécologie et d’Obstétrique (FIGO) staging score (early vs. advanced) was inversely correlated with serum selenium concentration (p=0.027).Conclusions: Serum selenium concentration and GPx activity was significantly lower in the cervical cancer patients. Our results demonstrate that selenium and GPx activity may have an important role in the carcinogenesis of cervical cancer. Keywords: Cervical cancer, glutathione peroxidase activity, selenium DOI: 10.15850/ijihs.v4n2.833